2017
DOI: 10.3390/polym9090456
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Bulk Heterojunction Prepared by Sequential Deposition of Nanostructured Polymer and Fullerene

Abstract: Abstract:A morphologically-stable polymer/fullerene heterojunction has been prepared by minimizing the intermixing between polymer and fullerene via sequential deposition (SqD) of a polymer and a fullerene solution. A low crystalline conjugated polymer of PCPDTBT (poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta [2,1-b;3,4-b ]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)]) has been utilized for the polymer layer and PC 71 BM (phenyl-C 71 -butyric-acid-methyl ester) for the fullerene layer, respectively. Firstly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…This structure, termed a sequentially deposited BHJ (sq-BHJ), has been used in fullerene-based OSCs, sometimes yielding quantum efficiencies comparable to an as-cast BHJ (c-BHJ) based on D:A co-deposition. 17,18,[27][28][29][30][19][20][21][22][23][24][25][26] For example, the state-of-the-art sq- With fullerene-based semiconductors remaining the archetypal electron acceptor for OSCs, the recent fast advancement of high-performance non-fullerene acceptors (NFAs) has motivated a careful evaluation of the future direction of OSC research. [31][32][33][34][35] Beginning in 2015, the PCEs of champion NFA-based single-junction OSCs have been higher than those fabricated using fullerenes, and now stands at an impressive 14%.…”
Section: Introductionmentioning
confidence: 99%
“…This structure, termed a sequentially deposited BHJ (sq-BHJ), has been used in fullerene-based OSCs, sometimes yielding quantum efficiencies comparable to an as-cast BHJ (c-BHJ) based on D:A co-deposition. 17,18,[27][28][29][30][19][20][21][22][23][24][25][26] For example, the state-of-the-art sq- With fullerene-based semiconductors remaining the archetypal electron acceptor for OSCs, the recent fast advancement of high-performance non-fullerene acceptors (NFAs) has motivated a careful evaluation of the future direction of OSC research. [31][32][33][34][35] Beginning in 2015, the PCEs of champion NFA-based single-junction OSCs have been higher than those fabricated using fullerenes, and now stands at an impressive 14%.…”
Section: Introductionmentioning
confidence: 99%
“…1, a8-9) fullerene small molecules, paired with lower band gap conjugated polymers, permitting increased efficiencies up to almost 9%. 23,25,26,30,155,[173][174][175][176][177][178][179][180][181][182][183][184][185][186] Recently, NFAs have been integrated into spin casted bilayer devices, enabling PCEs in excess of 10%. 28,29,44,49,59,123,125,126,129,130,133,[187][188][189][190] One example of a NFA system is PBTB-TFS1 ( Fig.…”
Section: Lbl Opv Device Fabrication By Sequential Spin Coating Processesmentioning
confidence: 99%
“…59 Cui et al demonstrated that solubility and solvent choice are key for high performing LbL OPV devices. 59 Numerous studies have since shown the pseudo-bilayer morphology is susceptible to variations in the solvent or cosolvent, 130,[144][145][146]157,167,168,170,173,175,177,187,189 but is also influenced by other parameters such as thermal annealing, 24,132,134,137,152,153,155,156,160,161,181,184,191,193,194 use of additives, 26,166,168,171,176,180,182 or addition of binary components to the donor polymer. 141,143,148,158,161 Cho et al explored how solvent choice influenced morphology and phase separation in P3HT layers.…”
Section: Lbl Opv Device Fabrication By Sequential Spin Coating Processesmentioning
confidence: 99%
“…The whole set of spectroscopic characteristics (both steady-state and time-resolved) will be performed to select the most promising constituents for host-guest systems. Second-order nonlinear susceptibility of poled metal-polymers, organo-polysilanes and their composites will be measured by SHG and electro-optical techniques [15]. Quantum-chemical calculations will be performed to estimate the first hyperpolarizability of the polymer's sub-units.…”
Section: Methodsmentioning
confidence: 99%